2021
DOI: 10.3390/pr9060943
|View full text |Cite
|
Sign up to set email alerts
|

Health and Housing Energy Expenditures: A Two-Part Model Approach

Abstract: Interest in the interaction between energy and health within the built environment has been increasing in recent years, in the context of sustainable development. However, in order to promote health and wellbeing across all ages it is necessary to have a better understanding of the association between health and energy at household level. This study contributes to this debate by addressing the case of Portugal using data from the Household Budget Survey (HBS) microdata database. A two-part model is applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Different from other EP measures, households in EP5 (meaning those using biomass as their main energy source) are significantly associated with a higher probability of having total, OOP and other health care expenditures but not with health care cost burden conditional on having any expenditures (Table A4). This finding is consistent with Lima et al (2021), who found that the use of and exposure to liquid 13 and solid fuels contribute to a higher probability of incurring health care expenditures.…”
Section: Alternative Measures Of Epsupporting
confidence: 92%
See 1 more Smart Citation
“…Different from other EP measures, households in EP5 (meaning those using biomass as their main energy source) are significantly associated with a higher probability of having total, OOP and other health care expenditures but not with health care cost burden conditional on having any expenditures (Table A4). This finding is consistent with Lima et al (2021), who found that the use of and exposure to liquid 13 and solid fuels contribute to a higher probability of incurring health care expenditures.…”
Section: Alternative Measures Of Epsupporting
confidence: 92%
“…Liquid fuels include domestic heating and lighting oil; such fuels are carbon-intensive energy alternatives similar to solid fuels(Lima et al, 2021).…”
mentioning
confidence: 99%
“…Lima et al [11] shed new light on the association between health and energy use at the household level for the Portuguese case, using data from the Household Budget Survey (HBS) database. The authors used a two-part model to estimate health expenditures based on energy-related expenditures, controlling for other socioeconomic variables.…”
mentioning
confidence: 99%